2020
DOI: 10.1016/j.tcb.2020.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Cristae Membrane Dynamics – A Paradigm Change

Abstract: Mitochondria are dynamic organelles that have essential metabolic and regulatory functions. Earlier studies using electron microscopy (EM) revealed an immense diversity in the architecture of cristaeinfoldings of the mitochondrial inner membrane (IM)in different cells, tissues, bioenergetic and metabolic conditions, and during apoptosis. However, cristae were considered to be largely static entities. Recently, advanced super-resolution techniques have revealed that cristae are independent bioenergetic units th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
91
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 116 publications
(154 reference statements)
0
91
0
1
Order By: Relevance
“…These ribbons of CV dimers are involved in the folding crista membrane [56]. It seems therefore that the intra-mitochondrial architecture is complex than initially believed, with MICOS, OPA1 and CV dimers playing a stru role, together with the abundance of non-bilayer cone-shaped phospholipids, such a diolipin and phosphatidylethanolamine [53,57,58].…”
Section: Oxphos Optimization By the Inner Membrane Architecturementioning
confidence: 99%
“…These ribbons of CV dimers are involved in the folding crista membrane [56]. It seems therefore that the intra-mitochondrial architecture is complex than initially believed, with MICOS, OPA1 and CV dimers playing a stru role, together with the abundance of non-bilayer cone-shaped phospholipids, such a diolipin and phosphatidylethanolamine [53,57,58].…”
Section: Oxphos Optimization By the Inner Membrane Architecturementioning
confidence: 99%
“…depletion results in increased CJ diameter, increased cytochrome c release from the ICS as well as a loss of membrane potential ( [64,67].In addition to this case, the right concentration of ions in the different compartments is essential for maintaining cellular homeostasis, for example by signalling and initiating cell death programs when required, this will be an essential problem of future studies.…”
Section: Accepted Articlementioning
confidence: 99%
“…Previous studies have shown an interplay of MICOS subunits and CL. It was demonstrated that CL is required for assembly of MIC27, which is a subunit of the MIC10 sub-complex and belongs to apolipoprotein family [67,86]. Localization of Mic27 and mitochondrial morphology was analyzed in wild type (WT) cells and cells lacking the mitochondrial CL synthesis enzyme, Crd1.…”
Section: Accepted Articlementioning
confidence: 99%
See 2 more Smart Citations